BRCA1/2 mutation screening and LOH analysis of lung adenocarcinoma tissue in a multiple-cancer patient with a strong family history of breast cancer - Boettger, Melanie Barbara (BioMed Central, 2003)
BACKGROUND: Germline mutations in BRCA1/2 greatly elevate risks of breast and ovarian cancers, but the role of these genes in tumourigenesis of other cancer types is still being investigated. OBJECTIVE: We report on an investigation of BRCA1/2 mutations and their loss of heterozygosity (LOH) in a patient with a strong family history of breast cancer who was diagnosed with consecutive primary cervical, ovarian and lung carcinomas. METHODS AND RESULTS: BRCA1/2 mutation screening of the proband revealed a common familial breast- and ovarian cancer-associated germline BRCA2 mutation (3034del4bp). We then performed LOH analysis for BRCA2 in lung adenocarcinoma tissue of the patient. Using the laser-capture microdissection (LCM) technique, we obtained pure populations of neoplastic cells from which DNA could be extracted. Mutation analysis by denaturing high-performance liquid chromatography (DHPLC) and direct sequencing revealed loss of the mutant allele in the adenocarcinoma tumour tissue. CONCLUSION: To our knowledge, this is the first report of investigation for LOH for BRCA2 in primary lung adenocarcinoma tissue of a patient with multiple primary tumours related to a familial germline BRCA2 mutation. Interestingly, it was the mutant, not the wild-type, allele which was lost in the lung adenocarcinoma tissue.